(untitled) (Philologia, 2021)
The paper explores possible interpretations of the function of the elements of the critical apparatus deployed in the narrative discourse in the novel Pale Fire by Vladimir Nabokov. In particular, it addresses critical issues raised by the fact that there are multiple narrative levels in the novel originating from different sources, all of which may at some point be identiﬁed as authors, and explores the idea that such positioning of the narrative levels implies, or in fact generates different “realities”, which all belong to the same work of ﬁction